Can severe asthmatic patients achieve asthma control? A systematic approach in patients with difficult to control asthma followed in a specialized clinic. Issue 1 (December 2016) - Athanazio, Rodrigo; Carvalho-Pinto, Regina; Fernandes, Frederico; Rached, Samia; Rabe, Klaus; Cukier, Alberto; Stelmach, Rafael
Abstract Background Despite advances in asthma treatment, severe asthma (SA) still results in high morbidity and use of health resources. Our hypothesis was that SA patients would achieve adequate control with a systematic protocol, including oral corticosteroids, budesonide/formoterol maintenance and reliever therapy and a multidisciplinary approach to improve adherence. Methods Non-controlled (NC) SA patients were enrolled to receive 2 weeks of oral corticosteroids and 12 weeks of formoterol + budesonide. Assessments included asthma control questionnaire (ACQ), asthma control test (ACT), daily symptom diary, lung function and health-related quality of life (HRQoL) questionnaires. Results Of 51 patients, 13 (25.5%) achieved control. NC patients had higher utilization of health resources and higher exacerbation rates. Both controlled (C) and NC patients had significantly reduced ACQ scores after oral corticosteroid treatment. After 12 weeks, C patients continued improving. NC patients did not have significant changes. A similar pattern was found regarding lung function, use of rescue medication, and days free of symptoms. After 2 weeks of oral corticosteroids, an increase occurred in those who achieved the ACQ cut off; however, 53.8% of C patients had an ACQ < 1.57 versus 21.1% of NC patients (p = 0.03). Both groups had low HRQoL at baseline with improvement after intervention. Conclusions Despite rigorous, optimized follow-up treatment, 75% of SA patients did not achieve adequate symptom control and presented with impaired quality of life. Conversely, application of a low-cost, easy to implement systematic protocol can prevent up to 25% of SA patients from up-titrating to new and complex therapies, thus reducing costs and morbidity. Trial registration Retrospectively registered at ClinicalTrial.gov on 22 February 2010 (NCT01089322 ).